2009
DOI: 10.1111/j.1551-2916.2009.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Consolidation of BaAl2Si2O8:Eu: Development of an Integrated Process for Luminescent Smart Ceramic Materials

Abstract: A novel, integrated, fast, and inexpensive process for the preparation of dense Ba(1−x)EuxAl2Si2O8 thin ceramic specimens for damage sensor applications is reported. The processing approach involves a combination of combustion synthesis for the preparation of the powders and spark plasma sintering (SPS) for the consolidation of the specimens to densities close to 100% of relative density. The synthesis of the porous powders by combustion resulted in particle (agglomerate) sizes that were on average 421 nm, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 74 publications
(118 reference statements)
2
36
0
Order By: Relevance
“…The temperature read by both pyrometers was recorded at 1 s intervals. More details and specific capabilities of the spark plasma sintering technique are discussed elsewhere [60][61][62][63][64]. After sintering, samples were fractured, and the specimens imaged with a scanning electron microscope (FEIe Quanta 200F, FEI Company, Hillsboro, OR).…”
Section: Methodsmentioning
confidence: 99%
“…The temperature read by both pyrometers was recorded at 1 s intervals. More details and specific capabilities of the spark plasma sintering technique are discussed elsewhere [60][61][62][63][64]. After sintering, samples were fractured, and the specimens imaged with a scanning electron microscope (FEIe Quanta 200F, FEI Company, Hillsboro, OR).…”
Section: Methodsmentioning
confidence: 99%
“…First, 50 mL of deionized water were poured in a beaker and a few drops of HCl were added to maintain the pH of the solution at approximately 1. This beaker was placed in a glove box and 4.9571 g of WCl 6 were added to prepare a solution of WCl 6 (solution A). Immediately after the addition of the WCl 6 , a few white fumes were observed being released from the beaker.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been found that for some materials, the particle (i.e., agglomerate) size of powders tends to define the final grain size of the dense compact under typical SPS conditions. [5,6] Thus, characterizing the crystallite size of a powder from X-ray diffraction or transmission electron microscopy is necessary, but not sufficient, in order to determine the sintering behavior of a powder and the final grain size after completion of sintering.…”
Section: Introductionmentioning
confidence: 99%
“…Additional details on the SPS process can be found elsewhere. [21][22][23][24][25] Phase development/devitrification of the samples was characterized by X-ray diffraction (Ultima IV, Rigaku, Japan) using CuKα radiation, a step size of 0.02 degrees 2θ, a count time of 1 s, and scanning from 20 to 80 degrees 2θ. Densities of the samples were evaluated by the Archimedes method using a Mettler Toledo Density Kit (Mettler Toledo, Columbus, OH).…”
Section: Methodsmentioning
confidence: 99%